The psychiatric inpatient physical health assessment sheet (PIPHAS): a useful tool to improve the speed, efficiency, and documentation of physical examination in new psychiatric inpatients. Issue 1 (23rd January 2015) - Pettipher, Alexander; Ovens, Richard
Abstract: There is increased morbidity and mortality among patients suffering from mental illness. This is believed to be multi-factorial. Poor access to healthcare, the stigma of mental illness, reduced clinic attendance, lifestyle factors, and side effects of medications are cited as possible contributing factors. It is therefore vital to perform a physical examination to identify previously undiagnosed conditions during the admission of a psychiatric inpatient. The Royal College of Psychiatrists recommends that all patients admitted to a psychiatric hospital should receive a full physical examination on admission, or within twenty-four hours of admission. A snapshot audit was carried out at Prospect Park Hospital in Reading, which highlighted that The Royal College of Psychiatrist's recommendation, along with Trust guidelines regarding physical examination were not being met, with only 78 out of 111 patients (70.3%) undergoing an examination during their admission. In addition to this, examinations were often poorly documented and not covering all examination domains. A psychiatric inpatient physical health assessment sheet (PIPHAS) was designed and introduced, providing a quick and standardised approach to the documentation of a physical examination. After the intervention was put into practice, its impact was assessed by performing a retrospective review of the admission clerking notes of the next 100 admissions to Prospect Park Hospital. Following the introduction of the PIPHAS form there was an increase in the number of patients undergoing physical examination on admission to hospital (75 out of 100 patients, 75%). There was also an increase in the thorough documentation of all examination domains (e.g. respiratory examination) for patients that had a completed PIPHAS form scanned within their medical records. This quality improvement project demonstrates that the PIPHAS form is a useful tool to improve the speed, efficiency, and documentation of a thorough physical examination in new psychiatric inpatients.